2018
DOI: 10.18203/2394-6040.ijcmph20184795
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 10-year cardiovascular risk using WHO/ISH risk prediction chart among urban population in Salem

Abstract: Background: Coronary vascular disease (CVD) risk estimation tools are a simple means of identifying those at high risk in a community and hence a potentially cost-effective strategy for CVD prevention in resource-poor countries. The WHO /ISH risk prediction charts provide approximate estimates of cardiovascular disease risk in people who do not have established coronary heart disease, stroke or other atherosclerotic disease.Methods: A total of 280 subjects between 40 to 70 years of age were included in this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…[ 20 ] The number of diabetics in India has more than doubled from 26 million in 1990 to 65 million in 2016. [ 21 ] This high prevalence of diabetes has also been shown among women in urban Salem (18%)[ 15 ] and also reflected in our study which found that one in every five women were diabetic and one-fourth in prediabetic stage. A study in Bangalore found 15.1% diabetes and 13.8% prediabetes among urban slum-dwelling women.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[ 20 ] The number of diabetics in India has more than doubled from 26 million in 1990 to 65 million in 2016. [ 21 ] This high prevalence of diabetes has also been shown among women in urban Salem (18%)[ 15 ] and also reflected in our study which found that one in every five women were diabetic and one-fourth in prediabetic stage. A study in Bangalore found 15.1% diabetes and 13.8% prediabetes among urban slum-dwelling women.…”
Section: Discussionsupporting
confidence: 82%
“…[ 8 ] However, a lower proportion was seen in two studies in Tamil Nadu. One in Salem, among women aged 40–70 years which found 6.5% high CVD risk[ 15 ] and the other in a village near Chennai among both men and women, where 6.25% had high CVD risk. [ 16 ] These geographic and rural/urban contextual differences have also been exhibited in a systematic analysis of coronary heart disease (CHD) rates in India, where CHD rates were higher in rural North India and urban South India,[ 17 ] owing to commonality in patterns unhealthy diet and physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted by Premanandh K et.al. 17 also showed that abdominal obesity and alcohol consumption were significantly associated with higher CVD risk.…”
Section: Discussionmentioning
confidence: 90%
“…A study conducted in Salem ( Premanandh K, Shankar R (2018) ) revealed that most of subjects had low CVD risk. 4 A study was conducted in Malaysia (2013) with a cross-sectional design. Total 196 subjects (aged 40-70 years) were selected who was attending outpatient clinic, USM hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Salem (Premanandh K, Shankar R (2018)) also showed that abdominal obesity and alcohol consumption were significantly associated with higher CVD risk. 4 A study with community based approach and cross-sectional design was carried out in rural areas of Mysuru concluded that High BMI, abdominal obesity, smoking and alcohol is significantly related to Increasing the risk of CVD. 9…”
Section: Discussionmentioning
confidence: 99%